Economic Integration in the Maghreb : An Untapped Source of Growth - Kireyev, Alexei; Nandwa, Boaz.; Ocampos, Lorraine; Sarr, Babacar (Washington, D.C. : International Monetary Fund, 2019)
Individual countries of the Maghreb have achieved substantial progress on trade, but, as a region they remain the least integrated in the world. The share of intraregional trade is less than 5 percent of their total trade, substantially lower than in all other regional trading blocs around the world. Geopolitical considerations and restrictive economic policies have stifled regional integration. Economic policies have been guided by country-level considerations, with little attention to the region, and are not coordinated. Restrictions on trade and capital flows remain substantial and constrain regional integration for the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet